2016
DOI: 10.1111/chd.12425
|View full text |Cite
|
Sign up to set email alerts
|

Trends, microbiology, and outcomes of infective endocarditis in children during 2000-2010 in the United States

Abstract: The incidence of IE in children has remained unchanged in the United States during the 11-year study period. Among culture-positive patients there was a significant decrease in Staphylococcal IE and a significant increase of Streptococcal IE. Staphylococcal IE was associated with increased LOS and highest mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
76
1
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(87 citation statements)
references
References 24 publications
6
76
1
4
Order By: Relevance
“…This comes in line with the overall microbiologic profile of IE in adults (staphylococci, 42%; and streptococci, 29%)59 and in pediatrics (staphylococci, 43%; and streptococci, 40%) 60. Similar patterns were also reported in prosthetic valve endocarditis (PVE; staphylococci, 40%; and streptococci, 22%)59 and in pulmonary surgical conduit IE (staphylococci, 53%; and streptococci, 43%) 47.…”
Section: Discussionsupporting
confidence: 81%
“…This comes in line with the overall microbiologic profile of IE in adults (staphylococci, 42%; and streptococci, 29%)59 and in pediatrics (staphylococci, 43%; and streptococci, 40%) 60. Similar patterns were also reported in prosthetic valve endocarditis (PVE; staphylococci, 40%; and streptococci, 22%)59 and in pulmonary surgical conduit IE (staphylococci, 53%; and streptococci, 43%) 47.…”
Section: Discussionsupporting
confidence: 81%
“…All studies were conducted in tertiary urban or teaching hospitals. Among studies conducted in highincome settings, 15 were in European countries, [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] 19 in the United States of America, [17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35] one in Australia, 36 three elsewhere in North America, [37][38][39] and three in Asia. [40][41][42] There were three nonrandomised interventional studies, 6,22,23 32 cohort studies, [2][3][4][5][7][8]...…”
Section: Epidemiology Of Perioperative Infections In High-income Counmentioning
confidence: 99%
“…These included acute respiratory tract infectionsupper respiratory tract infection, bronchiolitis, pneumonia, and respiratory syncytial virus infections 5,10,11,20,40 sepsis, 18 and infective endocarditis. 4,24,39,41 Among children with cardiac disease, the cumulative incidence of preoperative hospitalisation from respiratory syncytial virus (RSV) infection was 0.5% (2518/549,265) to 9.6% (58/602) in children <2 years of age with mortality of 1.9% of 8127 to 4.9% of 549,265 patients. 5,11,20,40 Risk factors for hospital admission due to acute respiratory tract infections were malnutrition, infant, male, chromosomal abnormalities, wheezing, inadequate respiratory syncytial virus prophylaxis, and sibling <11 years of age.…”
Section: Epidemiology Of Perioperative Infections In High-income Counmentioning
confidence: 99%
“…This was in contrast to American Heart Association (AHA) [2] and European Society of Cardiology (ESC) [3] guidelines issued around the same time, which continued to recommend antibiotic prophylaxis in certain high-risk cases, e.g., patients with prosthetic heart valves or who had had infective endocarditis previously. Although much research on the impact of guideline changes on the incidence of infective endocarditis has been conducted internationally [4][5][6][7][8][9][10][11][12][13][14][15], and in particular a study in England which showed an increase in cases following the NICE guideline change [6], no consensus has been reached, and in a 2016 update to their guidelines [16] NICE reaffirmed their previous position, while clarifying that doctors and dentists should still apply their clinical judgement on a case by case basis.…”
Section: Introductionmentioning
confidence: 99%